Room‐Temperature Synthesis of 2D Janus Crystals and their Heterostructures. Issue 50 (11th November 2020) - Trivedi, Dipesh B.; Turgut, Guven; Qin, Ying; Sayyad, Mohammed Y.; Hajra, Debarati; Howell, Madeleine; Liu, Lei; Yang, Sijie; Patoary, Naim Hossain; Li, Han; Petrić, Marko M.; Meyer, Moritz; et al.
Abstract: Janus crystals represent an exciting class of 2D materials with different atomic species on their upper and lower facets. Theories have predicted that this symmetry breaking induces an electric field and leads to a wealth of novel properties, such as large Rashba spin–orbit coupling and formation of strongly correlated electronic states. Monolayer MoSSe Janus crystals have been synthesized by two methods, via controlled sulfurization of monolayer MoSe2 and via plasma stripping followed thermal annealing of MoS2 . However, the high processing temperatures prevent growth of other Janus materials and their heterostructures. Here, a room‐temperature technique for the synthesis of a variety of Janus monolayers with high structural and optical quality is reported. This process involves low‐energy reactive radical precursors, which enables selective removal and replacement of the uppermost chalcogen layer, thus transforming classical transition metal dichalcogenides into a Janus structure. The resulting materials show clear mixed character for their excitonic transitions, and more importantly, the presented room‐temperature method enables the demonstration of first vertical and lateral heterojunctions of 2D Janus TMDs. The results present significant and pioneering advances in the synthesis of new classes of 2D materials, and pave the way for the creation of heterostructures from 2D Janus layers. Abstract : Janus crystals represent an exciting class of 2D materials with different atomic species on their upper and lower facets. Theories predict that this broken symmetry leads to a wealth of novel properties. A room‐temperature technique for the synthesis of a variety of Janus monolayers and their lateral and vertical heterostructures with high structural and optical quality is reported.